The Effectiveness of Career Decision Self-Efficacy Group Counseling to Improve Students’ Career Adaptability - Meilanda, Angga Yuda; Sugiyo, Sugiyo; Sunawan, Sunawan (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Career adaptability is an individual’s readiness which develops over time from the age of children, adolescents, to adults and functions to overcome predictable tasks and participate directly in the work environment and roles. Low adaptability of careers can cause individuals to have difficulty in preparing for their future careers. This study aimed to determine whether career decision self-efficacy (CDSE) group counseling effectively improves students’ career adaptability. It was an experimental study that used a randomized pretest-posttest control group design by selecting 18 of 360 students as the subjects of this study and dividing them into 2 groups, namely experimental and control groups. In analyzing the data, this study used Mixed MANOVA. Findings confirmed that career decision self-efficacy group counseling was effective in improving students’ career adaptability (F (1.16) = 1401.74, p < 0.01. This effectiveness could also be seen in the effect of time (F (2,32) = 462.18, p < 0.01), and the effect of the interaction between time and group (F (2,32) = 443.38, p < 0.01). Finally, the current study confirms that to improve students’ career adaptability, counselors or guidance and counseling teachers can apply CDSE to group counseling services.